The Performance of Listed Hedge Fund Firms - SUN, Lin (Institutional Knowledge at Singapore Management University, 2013)
We examine the impact of fund management company listing on hedge fund performance. We find that hedge funds managed by listed firms underperform those managed by unlisted firms by 1.89 per annum after adjusting for risk. Using an event study framework, we show that hedge fund performance deteriorates from 10.32 percent per year in the 36-month pre-listing window to 2.16 percent per year in the 36-month post-listing window. Over the same period, firm assets under management effectively double from US$1.54bn to US$3.04bn. There is no evidence to suggest that funds managed by listed firms are better able to manage operational risk and are therefore less likely to terminate fund operations. Our results shed light on the motives for exchange listing by hedge fund firms.